Penggunaan Aplikasi Berbasis Smartphone tentang Pengayaan Materi Kebugaran Jasmani di SMP Se-Kecamatan Kartasura - Saputra, Ardhian Bachtiar Panca; Putra Aji, Ranu Baskora (Universitas Negeri Semarang, 2023)
The purpose of this study is to describe the use of smartphone-based applications for learning physical fitness in grades 7–9. The research was carried out by junior high schools in Kartasura District, Sukoharjo Regency, Central Java. The data collection technique for this research used a questionnaire method with descriptive data analysis techniques using IBM Statistics 21. The results of this study indicate that the majority of respondents chose TKJI and SAQ Training Grade 8. Teacher knowledge on 7 physical fitness applications in the